An exploratory study of prevalence of mental retardation in mysore city - J, Bharath Raj (Journal of All India Institute of Speech and Hearing, 1971)
It is recognised long since that mental retardation is one of serious afflictions of mankind, in terms of its magnitude and dire consequences to the sufferer, his family and the society in which he lives. As elsewhere, this clinical condition remained outside the centre of interest, both for the professionals and the public in our country also. An awareness has now come among the related professional people to make a serious study of it, in all its ramifications. There has been of late, an increasing participation of various professional groups as Psychologists, Psychiatrists, Educationists, Paediatricians and Social Workers. The growing importance of this field is evidenced by the coming into being of an All India Association of Mental Retardation (A.I.A.M.R.) and the All India level conferences it successfully organised at Chandigarh in 1965, 1967 and at New Delhi in 1966, and the Indian Journal of Mental Retardation whose first volume appeared in 1968.